Define f ( x ) = k = 1 ∑ 2 0 1 6 k + 1 x k + 1 . If f ( 2 0 1 6 ) ( 1 0 0 ) can be evaluated as a × b ! where b is maximum, find a + b .
Bonus: If f ( x ) = k = 1 ∑ n k + 1 x k + 1 , find f ( n ) ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution ;) Please post solution Part 1 as well.
We know that f ( x ) = k = 1 ∑ 2 0 1 6 k + 1 x k + 1 = 2 x 2 + 3 x 3 + 4 x 4 + . . . + 2 0 1 7 x 2 0 1 7 ⇒ f 1 ( x ) = x + x 2 + x 3 + . . . + x 2 0 1 6 ⇒ f 2 0 1 6 ( x ) = k = 1 ∏ 2 0 1 5 k + ( k = 1 ∏ 2 0 1 6 k ) x Now, we get f 2 0 1 6 ( 1 0 0 ) = k = 1 ∏ 2 0 1 5 k + ( k = 1 ∏ 2 0 1 6 k ) ( 1 0 0 ) = ( k = 1 ∏ 2 0 1 5 k ) × [ 1 + 2 0 1 6 ( 1 0 0 ) ] = ( k = 1 ∏ 2 0 1 5 k ) × 2 0 1 6 0 1 The answer is now in the desired form ∴ 2 0 1 5 + 2 0 1 6 0 1 = 2 0 3 6 1 6 .
Problem Loading...
Note Loading...
Set Loading...
f ( x ) f ′ ( x ) f 2 ( x ) f 3 ( x ) f n ( x ) = k = 1 ∑ n k + 1 x k + 1 = k = 1 ∑ n k + 1 ( k + 1 ) x k = k = 1 ∑ n k x k − 1 = k = 1 ∑ n k ( k − 1 ) x k − 2 ⋯ ⋯ = k = 1 ∑ n ( k ) ( k − 1 ) ⋯ ( k − ( n − 2 ) ) x ( k − ( n − 1 ) )
Since first ( n − 2 ) terms of the summation will be zero we only have to calculate last two terms i.e:
= k = ( n − 1 ) ∑ n ( ( k ) ( k − 1 ) ⋯ ( k − ( n − 2 ) ) x ( k − ( n − 1 ) )
= ( n − 1 ) ! + x n ! = ( n − 1 ) ! ( 1 + n x )
In the given question, n = 2 0 1 6 , x = 1 0 0 . Putting we get 2 0 1 5 ! × ( 2 0 1 6 0 0 1 ) . Hence answer = 2 0 1 5 + 2 0 1 6 0 0 1 = 2 0 3 6 1 6 .